Managing Drawbacks in Unconventional Successful Glaucoma Surgery: A Case Report of Stent Exposure. (29th July 2015) - Fea, Antonio; Cannizzo, Paola Maria Loredana; Consolandi, Giulia; Lavia, Carlo Alessandro; Pignata, Giulia; Grignolo, Federico M.
Abstract : Traditional options in managing failed trabeculectomy (bleb needling, revision, additional incisional surgery and tube surgery) have a relatively high failure and complication rate. The use of microinvasive glaucoma surgery (MIGS) has generally been reserved to mild to moderate glaucoma cases, proving good safety profiles but significant limitations in terms of efficacy. We describe a patient who underwent MIGS (XEN Aquesys subconjunctival shunt implantation) after a prior failed trabeculectomy. After the surgery, the IOP was well controlled but as the stent was close to an area of scarred conjunctiva of the previous trabeculectomy, it became partially exposed. As a complete success was achieved, we decided to remove the conjunctiva over the exposed area and replace it by an amniotic membrane transplantation and a conjunctiva autograft. Six months after surgery, the unmedicated IOP is still well controlled with complete visual acuity recovery.